Controlled recrystallization for low-current RESET programming characteristics of phase-change memory with Ge-doped SbTe - Wu, Zhe; Zhang, Gang; Park, Youngwook; Kang, Stephen D.; Lyeo, Ho-Ki; Jeong, Doo Seok; Jeong, Jeung-hyun; No, Kwangsoo; Cheong, Byung-ki (AMER INST PHYSICS, 2011)
An investigation was conducted to examine the high RESET-current (I-RESET) problem of phase-change memory (PCM) using a fast growth-dominated Ge-doped SbTe (GeST). By examining material and device characteristics of GeST with varying Sb-to-Te ratio from 1.80 to 3.82, the growth rate of crystallization was found to play an important role in determining IRESET and SET speed of the device. Lower IRESET obtained with decreasing Sb-to-Te ratio was ascribed to lower growth rate leading to smaller degree of recrystallization during melt-quenching. With shrinkage of device dimensions, GeST-PCM of a lower Sb-to-Te ratio may become increasingly promising due to its lower IRESET and scaled SET speed. (C) 2011 American Institute of Physics. [doi: 10.1063/1.3641470]